2019
DOI: 10.1007/s12273-019-0563-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical thermal evaluation of laminated binary microencapsulated phase change material drywall systems

Abstract: Microencapsulated phase change materials (MEPCMs) have the potential for energy storage applications in buildings. However, current MEPCMs are limited by their singular phase change transitional temperatures and are therefore unable to satisfy all year seasonal energy storage applications. This study was focused on numerically assessing the energy saving potential of a binary MEPCM drywall system which is capable of operating within two different phase change transitional temperature ranges. In this study, Ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For the hysteresis effect with complete cycles of melting-freezing phase change, temperature change with time determines the liquid fraction equation used in the source term, as shown in Equations ( 4) and (5).…”
Section: Governing Equations and Hysteresismentioning
confidence: 99%
See 2 more Smart Citations
“…For the hysteresis effect with complete cycles of melting-freezing phase change, temperature change with time determines the liquid fraction equation used in the source term, as shown in Equations ( 4) and (5).…”
Section: Governing Equations and Hysteresismentioning
confidence: 99%
“…Hence, a hysteresis model is used to simulate the hysteresis effect and the transition between melting and freezing curves in cases of incomplete phase change, as shown in Figure 4. The hysteresis model and the liquid fraction transition curves are developed using the 0:00 1:00 For the hysteresis effect with complete cycles of melting-freezing phase change, temperature change with time determines the liquid fraction equation used in the source term, as shown in Equations ( 4) and (5).…”
Section: Governing Equations and Hysteresismentioning
confidence: 99%
See 1 more Smart Citation
“…One notable advancement in this field was made by Su et al [18], who found out that laminated binary MEPCM drywall could perform thermally better than a single MEPCM drywall system across different seasons. Huang et al [19] also synthesized multiple formstable PCMs based on confining ethylene glycole distearate (EGDS) within epoxy-based polymer matrix through photo-initiated polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulated phase change materials (MicroPCMs) have expanded the application and market prospects of phase change materials [ 1 , 2 , 3 , 4 ], which include textiles, dyeing and printing [ 5 , 6 , 7 ], building energy saving [ 8 , 9 , 10 ], microencapsulated phase change slurry [ 11 , 12 , 13 ] and composite foam [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%